Oligopolistic competition and search without priors - Parakhonyak, A (Oxford University Press, 2014)
In this article, I examine a model of oligopolistic competition in which consumers search for prices but have no knowledge of the underlying price distribution. The consumers' behaviour satisfies four consistency requirements and, as a result, their beliefs about the underlying distribution maximise Shannon entropy. I derive the optimal stopping rule and equilibrium price distribution of the model. Unlike in Stahl (1989), the expected price is decreasing in the number of firms. Moreover, consumers can benefit from being uninformed, if the number of firms is sufficiently large.